Liang-Ge decoction ameliorates acute lung injury in septic model rats through reducing inflammatory response, oxidative stress, apoptosis, and modulating host metabolism - He, Wenju; Xi, Qiang; Cui, Huantian; Zhang, Pingping; Huang, Rui; Wang, Taihuan; Wang, Dongqiang (Frontiers in Pharmacology, 2022)
Liang-Ge decoction (LG) has been used in the treatment of early stage of spesis and can ameliorate sepsis-associated lung injury. However, the mechanism of LG on sepsis-associated lung injury remains unknown. In this study, we established a rat model of sepsis-associated lung injury using the cecal ligation and puncture (CLP) method, and investigated the therapeutic effects of LG on lung injury in rats with sepsis. In addition, the anti-inflammatory, anti-oxidative and anti-apoptotic effects of LG on sepsis-associated lung injury model rats were evaluated. Besides, untargeted metabolomics was used to investigate the regulation of metabolites in rats with sepsis-associated lung injury after LG treatment. Our results showed that LG could decrease the wet/dry (W/D) ratio in lung and the total cell count and total protein concentration in bronchoalveolar lavage fluid (BALF) in septic model rats. Hematoxylin and eosin (HE) staining showed that LG reduced the infiltration of pro-inflammatory cells in lung. In addition, LG treatmment down-regulated the gene and protein expression of pro-inflammatory cytokins in lung tissue and BALF. The activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were increased and the level of methane dicarboxylic aldehyde (MDA) was decreased in lung tissue homogenate in septic model rats after LG treament. Moreover, the numbers of apoptotic cells in lung were reduced and the activity of lactic dehydrogenase (LDH) in BALF was decreased in septic model rats after LG treament. Untargeted metabolomics analysis showed that LG treatment affected the levels of 23 metabolites in lung in septic model rats such as citric acid, methionine, threonine, alpha-ketoglutaric acid, and inositol, these metabolites were associated with the glycine, serine and threonine metabolism, cysteine and methionine metabolism, inositol phosphate metabolism and citrate cycle (TCA cycle) pathways. In conclusion, our study demonstrated the therapeutic effetcts of LG on sepsis-associated lung injury model rats. Moreover, LG could inhibit the inflammatory response, oxidative stress, apoptosis and regulate metabolites related to glycine, serine and threonine metabolism, cysteine and methionine metabolism, inositol phosphate metabolism and TCA cycle in lung in sepsis-associated lung injury model rats.